Synthesis, structure and properties of a calcium oxonitridosilicate phosphor showing green or red luminescence upon doping with Eu2+ or Ce3+. Issue 37 (6th September 2019) - Schmidt, Robert; Ströbele, Markus; Romao, Carl P.; Enseling, David; Jüstel, Thomas; Meyer, Hans-Jürgen
Abstract : The new phase Li x Ca16− x Si17 N32− x O2+ x is an easy to make derivative of the so-called Ca16 Si17 N34 and a promising phosphor when doped with Eu 2+ or Ce 3+ . Abstract : The phase Li x Ca16− x Si17 N32− x O2+ x was synthesized by solid-state metathesis at 1050 °C in weld-sealed niobium ampoules. The crystal structure was solved from powder X-ray diffraction data in the space group F 4̄3 m ( a = 14.7391(1) Å, Z = 4); it is closely related to the previously reported structure of Ca16 Si17 N34 . The structure of Li x Ca16− x Si17 N32− x O2+ x is based on a complex network of [SiN4 ] tetrahedra with interstitial voids filled by Ca ions, partially substituted by Li. This Li substitution is charge-compensated by replacement of N by O in the structure. Theoretical calculations confirm that the unit cell volume decreases with increasing stoichiometric factor x . Europium doped samples of this compound show intense Eu 2+ emission at 536 nm on excitation with near-UV or blue radiation at 350–480 nm. Ce 3+ doping yields orange to red emission with two broad emission bands at 600 and 665 nm.